beta-Endorphin: stability, clearance behavior, and entry into the central nervous system after intravenous injection of the tritiated peptide in rats and rabbits. - Houghten, R A (1980)
Rabbits and rats were given intravenous injections of tritiated human beta-endorphin. The levels of beta-endorphin were followed by the decrease in radioactivity in the plasma of rats or rabbits and by the increase in radioactivity in the cerebrospinal fluid of the rabbit. The results were identical with the tritium label on either tyrosine-1 or -27. The plasma distribution times were 2 and 5 min in the rat and rabbit, respectively, with a later clearance time of approximately 1-8 hr. In the rat, approximately 50% of the radioactivity in the plasma was found to be intact human beta-endorphin 45 min after injection. Radioactivity appeared in the cerebrospinal fluid of the rabbit within 30 sec after injection and reached a plateau in approximately 60-90 min after injection. Approximately 75% of the radioactivity in the cerebrospinal fluid of the rabbit was intact human beta-endorphin. In the brain hemispheres of the rat and the rabbit, the only significant radiolabeled product was found to be radioactive tyrosine. Moreover, rat plasma levels of beta-endorphin decreased dramatically after hypophysectomy, which only slightly lowered the levels in the brain. It appears that beta-endorphin, upon entry into the plasma, is either not significantly taken up into the brain or is broken down with extreme rapidity upon entry into the brain, although it apparently does enter the cerebrospinal fluid.